The role of universities in the growth of Shenzhen’s digital creative economy - Cao, Yao (Curtin University, 2023)
This thesis explores the drivers of Shenzhen’s rapid economic growth in the context of the evolving digital creative economy and examines the role that universities are playing in this process. It concludes that entrepreneurial practices are expanding within the established and traditional Chinese higher education system as a result of local industries’ demands and government endorsement. This thesis provides an innovative perspective centred on universities to understand Shenzhen’s digital rise.